Ultra-sparse metasurface for high reflection of low-frequency sound based on artificial Mie resonances - Cheng, Y.; Zhou, C.; Yuan, B. G.; Wu, D. J.; Wei, Q.; Liu, X. J. (Nature materials, 2015)
Acoustic metamaterials offer great flexibility for manipulating sound waves and promise unprecedented functionality, ranging from transformation acoustics, super-resolution imaging to acoustic cloaking. However, the design of acoustic metamaterials with exciting functionality remains challenging with traditional approaches using classic acoustic elements such as Helmholtz resonators and membranes. Here we demonstrate an ultraslow-fluid-like particle with intense artificial Mie resonances for low-frequency airborne sound. Eigenstate analysis and effective parameter retrieval show two individual negative bands in the single-size unit cell, one of which exhibits a negative bulk modulus supported by the monopolar Mie resonance, whereas the other exhibits a negative mass density induced by the dipolar Mie resonance. The unique single-negative nature is used to develop an ultra-sparse subwavelength metasurface with high reflectance for low-frequency sound. We demonstrate a 0.15 λ -thick, 15%-filling ratio metasurface with an insertion loss over 93.4%. The designed Mie resonators provide diverse routes to construct novel acoustic devices with versatile applications. An ultraslow-fluid-like unit cell composed of acoustic channels, arranged in a zigzag shape, exhibits various tunable Mie resonances. It is used for the construction of a highly reflective metasurface that can efficiently block low-frequency sound.